On indecomposable and transitive systems of subspaces - Yakymenko, D. Yu. (Ukrains’kyi Matematychnyi Zhurnal, 2007)
We prove that the indecomposability of a system of subspaces of a finite-dimensional Hilbert space implies the transitivity of this system under the condition of the linear coherence of the corresponding system of orthogonal projectors.